Study on strength and fracture toughness of Al–Zn–Mg–Cu–Ti(–Sn) alloys (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
Strength and fracture toughness of Al–Zn–Mg–Cu–Ti(–Sn) alloys were studied with tensile tests and plane strain fracture toughness (KIC) tests. Detailed observations with optical, scanning electron and transmission electron microscopy were performed to analyze microstructure and fractured surfaces of the alloys. The results revealed that addition of Sn refines the solution-aging grain size of matrix and reduces coarsening rate of precipitate during aging. And narrower precipitation free zones and more discontinuous distribution of grain boundary precipitates were observed to appear in the Sn-containing alloy. These features of microstructure were believed to impart higher strength and fracture toughness of the Sn-containing alloy on overaging.